Prosesi Tradisi dan Budaya dalam Pemeliharaan Sapi Ternak di Kabupaten Karanganyar Jawa Tengah - Eko Purnomo; Atiqa Sabardila (Pustaka : Jurnal Ilmu-Ilmu Budaya, 2022)
The tradition of raising cattle needs to be preserved. Cows are often referred to as rojo koyo animals which means cows are one of the animals that can support the economic life of the community. This study aims to explain a series of traditions in cattle rearing in Suruhkalang Village. This research is included in qualitative research with a descriptive approach. The method used is descriptive, namely the researcher describes each data found. Sources of data in this study are cattle breeders in the village of Suruhkalang. The data in this study is a tradition carried out by cattle breeders in Suruhkalang Village. The data analysis technique in this study uses content analysis. Content analysis of the characteristics of the content of a message. The results showed that the people of Suruhkalang Village still maintain the tradition of raising cattle. The traditions that run cattle breeders are (1) the tradition of choosing cattle breeds, (2) the tradition of giving birth to cows, (3) the tradition of maintaining the health of cows, and (4) the tradition of bathing cows and cow equipment on Eid al-Fitr. Results Based on this research, it is hoped that the community will continue to uphold the tradition and by itself. With this research, we are able to explore the tradition of raising cattle in Suruhkalang Village as well as being able to document future generations.